2014
DOI: 10.1089/scd.2013.0578
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Electrospun Polymers Reveals Poly(3-Hydroxybutyrate) Fiber as a Superior Scaffold for Cardiac Repair

Abstract: The development of biomaterials for myocardial tissue engineering requires a careful assessment of their performance with regards to functionality and biocompatibility, including the immune response. Poly (3-hydroxybutyrate) (PHB), poly(e-caprolactone) (PCL), silk, poly-lactic acid (PLA), and polyamide (PA) scaffolds were generated by electrospinning, and cell compatibility in vitro, and immune response and cardiac function in vitro and in vivo were compared with a noncrosslinked collagen membrane (Col) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 44 publications
2
60
0
1
Order By: Relevance
“…Macrophages already activated by inflammatory signals will then respond to IL-4 and IL-13 by fusing to form multinucleated FBGCs. Both IL-4 and IL-13 have been shown to be secreted in larger quantities by macrophages cultured on electrospun silk scaffolds in vitro (24). Not surprisingly therefore, the implantation of silk materials often induces the formation of FBGCs.…”
Section: Mechanism Of Silk Degradationmentioning
confidence: 99%
“…Macrophages already activated by inflammatory signals will then respond to IL-4 and IL-13 by fusing to form multinucleated FBGCs. Both IL-4 and IL-13 have been shown to be secreted in larger quantities by macrophages cultured on electrospun silk scaffolds in vitro (24). Not surprisingly therefore, the implantation of silk materials often induces the formation of FBGCs.…”
Section: Mechanism Of Silk Degradationmentioning
confidence: 99%
“…Recently Castellano et al presented an extensive study on the ability for cardiac repair of various electrospun scaffolds including poly(3-hydroxybutyrate) (PHB), PCL, silk, PLLA, polyamide (PA) which were compared to a non-crosslinked collagen membrane that was used as control [114]. In vitro studies using mouse cardiac HL-1 cell line, cardiac fibroblasts and MSCs from dental pulp showed that PHB and PCL polymers allowed the greatest adhesion/growth of cells.…”
Section: Scaffolds Based On Other Polymeric Materialsmentioning
confidence: 99%
“…Plasma treated samples become more hydrophilic, allowing the attachment of cardiac cells as well as the desired proliferation and shape. Likewise Castellano et al utilized N 2 plasma for the introduction of polar groups onto the surface of PHB, PCL, PLLA, silk, PA electrospun scaffolds prior to cell culture [114].…”
Section: Post Treatment By Plasma Modificationmentioning
confidence: 99%
“…For instance, in the work of Castellano D. et al, collagen, poly(3-hydroxybutyrate), poly(ecaprolactone), poly-lactic acid and polyamide NFs were generated by electrospinning, being then transplanted into a rat MI model. Interestingly, poly(3-hydroxybutyrate) was the scaffold with the most beneficial reparative potential and positive remodeling capacity [85]. In another study polyester urethane urea NFs showed suitable mechanical properties and biocompatible characteristics, allowing cellular integration and endocardial endothelialization with minimal inflammation [86].…”
Section: Nanofibersmentioning
confidence: 99%